Comparison of skin toxicity in 26 Gray x 5 Fractions vs 40 Gray x 15 Fractions in early-stage post operative Breast cancer - Ateeqa Qayyum; Ahsan Mahmood; Bilal Asgher; Khurram khan; Kashif Ali Sarwar; Rabia Tariq (Medical Journal of South Punjab, 2024)
Objective: To compare the effects between hypo fractionated and ultra hypo fractionated radiation treatment in early breast cancer.Methodology: Cross-sectional Comparative study was started after getting approval from the ethical review committee of the hospital, the study was conducted at the Department of Radiation Oncology, Combined Military Hospital, Rawalpindi. Radiation induced skin changes were assessed periodically during treatment, post treatment and one month after treatment by history and local examination and degree of radiation dermatitis was categorized according to CTCAE.Results: The mean age of patients was 55 in this study. Radiation dermatitis was significantly affected by the stage, type of surgery and volume of the tissue receiving more than 107& RT dose, however no statistical difference was noted amongst the hypo and ultra hypo fractionated regimen. Conclusion: The study illustratedno significant skin toxicity observed in patients receiving hypo fractionatedor ultra hypo fractionated radiation treatment in early breast cancer.